Guimarães residents´ perceptions towards tourism impacts: a cluster analysis - Vareiro, Laurentina (2011)
The present study was designed to assess and segment local residents with respect to their perceived impacts of Guimarães tourism development. The residents of this municipality (located in the northern part of Portugal) are quite strong in their support to tourism. However, they do not keep a homogeneous perception of tourism impacts. A clusters analysis using data from a survey of 400 Guimarães residents’ has revealed the existence of three clusters, according the different degrees of perceived tourism impacts: the Skeptics - moderate in relation to the benefits (averages range from 2.89-3.74) and the ones more concerned with its costs (averages range from 2.86-3.74); the Moderately optimistic - very optimistic about the benefits of tourism (averages range from 3.74-4.51) and conscious of the costs (averages range from 2.71-3.49); the Enthusiasts - very optimistic about tourism benefits (averages range from 2.92-4.52) and little worried about its costs (averages range from 1.78-3.26). Following the data from the survey, the findings are discussed and a few conclusions are extracted. Keywords: cluster analysis, Guimarães, residents’ perceptions, tourism impacts.